2002
DOI: 10.1002/1521-3773(20020703)41:13<2304::aid-anie2304>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Cp∩N Complexes—Unusual Structural Features and Electronic Coupling in Highly Preorganized Bimetallic Systems

Abstract: Dedicated to Professor Lutz F. Tietze on the occasion of his 60th birthdayComplexes of cyclopentadienyl (Cp) ligands with functional amino or amido side chains are currently receiving enormous attention in organometallic chemistry. [1,2] While the donor substituent tethered to the Cp moiety usually serves a hemilabile chelate function in generic type A complexes, we recently put forward a novel approach in which a pyrazolate group in complexes of type B links two Cp units and acts both as an intramolecular N d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…Os(1)-C(1) 2.168(2) Os(1)-C (2) 2.177(2) Os(1)-C (3) 2.166(2) Os(1)-C(4) 2.172(2) Os(1)-C (5) 2.158(2) Os(1)-C (11) 2.238(2) Os(1)-C (16) 2.233 (2) Os (1)-C(17) 2.195(2) Os(1)-C (18) 2.246(2) Os(1)-C (19) 2.237(2) Os(1)-C 5 Me 5 centroid 1.788(2) Os(1)-fluorenyl centroid 1.861(2) C 5 Me 5 -Os(1)-fluorenyl centroid 178.7(1) Table 5 Selected bond lengths (Å ) and angles (°) for 4…”
Section: 38%mentioning
confidence: 99%
“…Os(1)-C(1) 2.168(2) Os(1)-C (2) 2.177(2) Os(1)-C (3) 2.166(2) Os(1)-C(4) 2.172(2) Os(1)-C (5) 2.158(2) Os(1)-C (11) 2.238(2) Os(1)-C (16) 2.233 (2) Os (1)-C(17) 2.195(2) Os(1)-C (18) 2.246(2) Os(1)-C (19) 2.237(2) Os(1)-C 5 Me 5 centroid 1.788(2) Os(1)-fluorenyl centroid 1.861(2) C 5 Me 5 -Os(1)-fluorenyl centroid 178.7(1) Table 5 Selected bond lengths (Å ) and angles (°) for 4…”
Section: 38%mentioning
confidence: 99%
“…Comparison of the molecular structures of K[LNi I 2 ] ( 2 K ) and K[L(Ni II ‐H) 2 ] ( 1 K ) shows that the most conspicuous difference is the position of the K + cation: In 1 K the K + is located within the plane defined by the pyrazolate‐bridged dinickel dihydride core and in between the two flanking aryl rings of the 2,6‐disopropylphenyl (dipp) substituents at distances indicative of cation‐π interactions [18a] . In contrast, in 2 K the K + is located above the pyrazolate [20] and is additionally ligated by four THF molecules (the structure of 2 Na is very similar, but the Na + has only two THF ligands; Figure S9). This striking difference may reflect attractive K + ⋅⋅⋅hydride interactions in 1 K that are now absent in the double “T”‐shaped dinickel(I) complex 2 K , in line with the stabilizing role of K + with respect to H 2 elimination from 1 K which has a much higher activation barrier than H 2 elimination from 1′ .…”
Section: Resultsmentioning
confidence: 99%
“…There have been extensive studies in the field of Schiff base macrocyclic complexes since they were first reported more than 40 years ago because of their particular properties and potential applications in the fields of magnetism, catalysis, artificial receptors, biological activities, and so on. Up to now, metal‐free and metal‐ion template methods have been used to prepare a variety of macrocyclic Schiff base metal complexes, but the latter method has proved more effective .…”
Section: Introductionmentioning
confidence: 99%